Diet composition and plastic ingestion in Poecilia reticulata from urban streams - Selinger, Amanda; Costa, João Henrique Alliprandini da [UNESP]; Sandri, Letícia Mazzuco; Wolff, Luciano Lazzarini; Souza, Ursulla Pereira; Silveira Jr, Landulfo; Delariva, Rosilene Luciana (Springer Nature, 2024)
Fish are excellent bioindicators and can reveal the presence of plastic in the environment. Diagnosing the composition and abundance of polymers in the fish diet makes it possible to evaluate their point sources and possible trophic transfers. We aimed to use the gastrointestinal contents of Poecilia reticulata in subtropical urban streams to detect the occurrence, shape, color, size, and chemical composition of polymers. For this, the diet of 240 individuals was analyzed using the volumetric method, and the microplastics (MPs; < 5 mm) recorded were characterized using Raman spectroscopy. Individuals predominantly consumed organic detritus and aquatic macroinvertebrates, with higher proportions of Diptera. A total of 111 plastic particles (< 0.5 to 12 mm) were recorded, and a subset of 14.4% was subjected to a micro-Raman spectrometer (830 nm excitation). The occurrence of polyethylene terephthalate (PET) and polypropylene (PP) with phthalocyanine dye was recorded. Some fragments could not be identified by Raman, but they contained indigo blue dye. Poecilia reticulata had a predominantly detritivorous diet with a record of plastic consumption, reflecting environmental pollution. Our results demonstrate that individuals of P. reticulata have ingested MPs in urban streams. This reinforces the need for future studies on the relationship between the presence of MPs in fish and the level of pollution in streams, comparisons with species of different feeding habits, and the potentially harmful effects on the entire biota.
Keywords: Chemical composition; Freshwater fish; Microplastic; Polyethylene terephthalate; Polymers; Polypropylene; Raman spectroscopy